Septic Arthritis of the Atlanto-Occipital Joint Caused By S. Intermedius in a 5-Year-Old Girl: A Case Report. Issue 3 (21st December 2022) - Di Siena, Andrea; Passone, Eva; Rodofile, Federica; Piccinin, Giada; Cereser, Lorenzo; Merelli, Maria; Cogo, Paola
Abstract : Septic arthritis of the atlanto-occipital joint caused by Streptococcus intermedius is extremely rare. We present the first case report of this entity in a fully immunocompetent 5-year-old girl. The magnetic resonance imaging and blood tests were consistent with septic arthritis, so she started empirical antibiotic therapy. Septic arthritis should be excluded in children with torticollis, fever and neck pain.